A comparison of the laryngeal mask airway with the facemask and oropharyngeal airway for manual ventilation by first responders in children. - Blevin, A; McDouall, S; Rechner, J; Saunders, T; Barber, V; Young, J; Mason, D (2009)
In adults, first responders to a cardiopulmonary arrest provide better ventilation using a laryngeal mask airway than a facemask. It is unclear if the same is true in children. We investigated this by comparing the ability of 36 paediatric ward nurses to ventilate the lungs of 99 anaesthetised children (a model for cardiopulmonary arrest) using a laryngeal mask airway and using a facemask with an oropharyngeal airway. Anteroposterior chest wall displacement was measured using an ultrasonic detector. Nurses achieved successful ventilation in 74 (75%) of cases with the laryngeal mask airway and 76 (77%) with facemask and oropharyngeal airway (p = 0.89). Median (IQR [range]) time to first breath was longer for the laryngeal mask airway (48 (39-65 [8-149])) s than the facemask/airway (35 (25-53 [14-120]) s; p < 0.0001). In 10 cases (10%) the lungs were ventilated using the laryngeal mask airway but not using the facemask/oropharyngeal airway. We conclude that ventilation is achieved rapidly using a facemask and oropharyngeal airway, and that the laryngeal mask airway may represent a useful second line option for first responders.